Impact of Workforce Diversity towards Organizational Performance: A Moderating Role of Organizational Nature - Thapa, Roshan; Adhikari, Pratima; Upadhyay, Pramod Raj (Nepalese Journal of Management Science and Research, 2025)
This study aimed to measure the impact of workforce diversity on organizational performance within Nepalese commercial banks. Employing a descriptive and explanatory design, researchers utilized descriptive and inferential statistics to analyze data from 356 employees across head and main offices, measuring diversity through gender, age, education, ethnicity, and culture. Findings revealed a significant positive impact of all diversity dimensions on organizational performance, while moderation analysis indicated no significant effect of the bank's nature on this relationship. These results suggest that Nepalese commercial banks can enhance performance by prioritizing workforce diversity, highlighting the consistent benefits of diversity management across different bank types within the industry.